The Evolution of Elder Housing Design and Development - Gallagher, John (Maine Policy Review, 2015)
Maine faces a growing number of elderly households as the baby boomer generation ages, which will have a major impact on housing. John Gallagher discusses the availability of affordable housing for elder adults, and what is being done to address the widening gap between the needs and wants of elders with limited financial resources and what will actually be available to them.